Adaptation and Representation of Narcissistic Desires of Calon Arang's Text in Bali - Koes Yuliadi (Journal of Urban Society's Arts, 2022)
Rangda and Barong appear a lot in performing art, paintings, and tattoos in Bali.  The sacred rituals involving the two creatures always attract attention—likewise forms of performances and crafts for tourists.  Historically the existence of Rangda and Barong started from the text of Calon Arang, which initially came from the island of Java in Indonesia.  This fact shows how the Balinese people attach themselves to myths and then develop them in creative works.  The relationship between the narrative text and visualization will be the material to see what desires are behind their consciousness and unconsciousness in understanding the Calon Arang.  There is an antagonistic offer on the characterizations and the creative process that perceives Calon Arang's story. The process of studying the object uses a qualitative method. In a time, observe and be directly involved in the Rangda and Barong ceremonies, see these figures' performances, visit markets and art galleries, and interview Balinese artists and cultural figures.  This process concludes that the continuous adaptation process based on the Calon Arang text involves the spiritual and creative power of the Balinese people as part of their narcissistic and analytic desires. Rangda and Barong always provide new phenomena in creative works with antagonistic ideas. Analyzing this data is very important to understand the concepts created, outcomes, and the spirituality of the interwoven in the development of Balinese art. Adaptasi dan Representasi Hasrat Narsis Teks Calon Arang di Bali. Rangda dan Barong merupakan figur yang sering terlihat pada pertunjukan seni, lukisan, dan tato di Bali. Agenda ritual sakral yang melibatkan keduanya selalu menarik perhatian. Demikian juga ketika ia muncul dalam bentuk pertunjukan dan kerajinan untuk wisatawan. Secara historis keberadaan Rangda dan Barong tidak bisa dilepaskan dari teks Calon Arang yang pada walnya berasal dari Pulau Jawa di Indonesia. Kenyaaan ini menunjukkan bagaimana keterikatan masyarakat Bali dengan mitos dan kemudian mengembangkannya dalam karya kreatif. Relasi teks naratif dan visualisasnya akan menjadi bahan untuk melihat hasrat apa yang ada di balik kesadaran dan ketidaksadaran mereka dalam menghayati Calon Arang. Terlihat adanya tawaran antagonistik pada penokohan dan proses kretif yang merpersepsi cerita Calon Arang. Proses pengkajian objek di atas menggunakan metode kualitatif.  Selain mengamati dan terlibat langsung dalam upacara Rangda dan Barong, melihat pertunjukan yang melibatkan figur tersebut, mengunjungi pasar dan galeri seni, juga wawancara dengan beberapa seniman dan budayawan Bali. Proses ini memberikan simpulan bahwa proses adaptasi yang berkenajutan berdasar teks Calon Arang melibatkan daya spiritual dan kreatif masyarakat Bali sebagai bagian dari hasrat narsistik dan anaklitik. Rangda dan Barong selalu memberikan fenomena baru dalam karya kreatif dengan berbagai gagasan yang antagonistik. Menganalisis data ini sangat menarik untuk memahami gagasan penciptaan, keberlanjutan karya, dan jalinan spiritualitas dalam perkembangan seni Bali hingga saat ini.